An Empirical Research regarding the Food Waste Phenomenon in Romania Compared to Other Countries from European Union - Marian Iulian NEDELCU (Revista de Management Comparat International)
The negative effects generated by the food waste, show that this phenomenon has become a stringent problem of the century we are living in, a social, economic and natural problem with a significant impact at global level. This food waste phenomenon, both at the European Union level and at the Romania level appears mostly within the households and services sector, and under these circumstances, this research represents a comparative analysis of the actual situation regarding the food waste in those two sectors, in European Union and in Romania, illustrating the evolution of this problem over time, based on relevant information from sources as: Eurostat, articles, reports from some European institutions and bodies.